Evidence for the effects of land use on freshwater ecosystems in New Zealand. Issue 3 (2nd July 2020) - Larned, Scott T.; Moores, Jonathan; Gadd, Jenni; Baillie, Brenda; Schallenberg, Marc
ABSTRACT: To meet the challenges of preventing and reversing adverse effects of land use on ecosystems, management actions need to be founded on strong evidence. We used the pressure-state-impact (PSI) framework to assess evidence of land-use effects on New Zealand freshwater ecosystems. The evidence consisted of published quantitative and categorical associations linking land-use pressures to state changes and ecological impacts in rivers, lakes and aquifers. There was substantial evidence of land-use effects, particularly where land use/land cover (LULC) classes were used as pressure variables. Proportions of catchment area in urban and pastoral LULC were consistently, positively correlated with contaminant levels in water bodies and negatively correlated with ecological-health indicators. Other consistent PSI associations included positive correlations between cattle stocking rates and river contaminant levels, increased fine sediment and decreased ecological-health scores in rivers following forest harvest, and increased river contaminant levels at sites with stock access. Despite these consistent associations, the evidence base has four general shortcomings that should be addressed: (1) inadequate integration of data and models that link land use and contaminant loss to state changes and impacts in freshwater ecosystems; (2) weak inferences based on LULC; (3) reliance on categorical PSI associations; (4) gaps in reported PSI associations.